Incentivizing Farmers to Invest in Quality through Quality‐Based Payment. Issue 10 (4th August 2021) - Ayvaz‐Çavdaroğlu, Nur; Kazaz, Burak; Webster, Scott
Abstract : We consider a for‐profit cooperative that sets a quality‐based payment to its risk‐averse farmers in order to incentivize them to invest in quality improvements. The quality of the farmer's harvest is affected by his investments during the growing season. To satisfy both the farmer and the cooperative, the payment must be competitive with the open‐market prices. Cooperatives often set payments that mimic the open‐market prices; however, this practice fails to incentivize farmers to invest in quality. Our work is motivated by the evidence of farmer underinvestment in crop quality in the olive oil industry. We define and analyze a model of this system where farmers operate under random yield, quality, and open‐market price. We find that farmers consistently underinvest in crop quality under the payment policy that mimics the open‐market prices because (1) the cooperative can command a higher retail price than a farmer and (2) farmers are risk averse. We propose two alternative payment policies that are new to the agricultural literature, both of which can coordinate farmer decisions with the system but differ in terms of ease of implementation and susceptibility to risk aversion. We identify an easy‐to‐implement policy that can lead to meaningful gains when introduced in conjunction with crop insurance. We calibrate our model using data from the olive oil industry in Turkey and find a profit improvement of 10–15% over the current open‐market payment approach.